Variance of the Flexure Model Predictions With Rejuvenated Volcanism at Kīlauea Point, Kaua‘i, Hawai‘i - Thordarson, Thor; Garcia, Michael O. (Frontiers in Earth Science, 2018)
The origin of rejuvenated volcanism on mantle plume related oceanic islands remains controversial. One commonly cited model is decompressional melting related to plate flexure from the rapid loading of the lithosphere by the formation of a shield volcano above the plume stem. This model provides testable predictions about the timing and subsidence history of the island. Here we evaluate the flexure model by examining the products of three well dated rejuvenation stage eruptions at Kīlauea Point, Kaua‘i, (Hawaii); the 2.65 ± 0.35 Ma Mōkōlea Point lava, 1.67 ± 0.11 Ma for Crater Hill tuff cone and 0.69 ± 0.03 Ma for Kīlauea Point lava events. These eruptions record the flexure of the island over a 2 Ma period, the longest sequence of rejuvenated volcanism within the Hawaiian Islands. These three eruptions, including two subaerial flows (the Mōkōlea Point and Kīlauea Point lavas) and the only phreatomagmatic vent structure on Kaua‘i (the Crater Hill tuff cone), document the progressive sinking and uplift of the island related to sea level as the island drifted away from the Hawaiian hot spot at ∼10 cm/year. The timing of volcanism and the elevation of Kīlauea Point relative to sea level are inconsistent with the predictions of the flexural melting model. These new results indicate that decompression melting cannot be the sole driver for rejuvenated volcanism on Kaua‘i. Additional explanations are needed to account for the timing and volume of rejuvenated volcanism in Hawai‘i.